2020
DOI: 10.1021/acsabm.0c00281
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembled Peptide Nanofibrils Designed to Release Membrane-Lysing Antimicrobial Peptides

Abstract: Membrane-disrupting antimicrobial peptides continue to attract increasing attention due to their potential to combat multidrug-resistant bacteria. However, some limitations are found in the success of clinical setting-based antimicrobial peptide agents, for instance, the poor stability of antimicrobial peptides in vivo and their short-term activity. Self-assembled peptide materials can improve the stability of antimicrobial peptides, but the biosafety of peptide-based materials is the main concern, although th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…This approach modifies the native AMP to alter its chemical characteristics (see Sections 2 and 3 , this review) so that under specific environmental conditions the peptides self-assemble/aggregate. These self-assembled multimers can form micelles (DP7-C), nanofibers ((QL) 6 -Melittin + (QL) 6 -K), lamellae (V 4 D) or fibrils (K 3 (FA) 4 K 3 ) ( Chen Y.-F. et al, 2019 ; Kornmueller et al, 2018 ; Sha et al, 2020 ; Zhang et al, 2018 ). To aid peptide self-assembly, AMP sequences can be modified or conjugated to self-assembling sequences or hydrophobic moieties (e.g., lipids or alkyl chains).…”
Section: Multi-unit Materials With Antimicrobial Activitymentioning
confidence: 99%
“…This approach modifies the native AMP to alter its chemical characteristics (see Sections 2 and 3 , this review) so that under specific environmental conditions the peptides self-assemble/aggregate. These self-assembled multimers can form micelles (DP7-C), nanofibers ((QL) 6 -Melittin + (QL) 6 -K), lamellae (V 4 D) or fibrils (K 3 (FA) 4 K 3 ) ( Chen Y.-F. et al, 2019 ; Kornmueller et al, 2018 ; Sha et al, 2020 ; Zhang et al, 2018 ). To aid peptide self-assembly, AMP sequences can be modified or conjugated to self-assembling sequences or hydrophobic moieties (e.g., lipids or alkyl chains).…”
Section: Multi-unit Materials With Antimicrobial Activitymentioning
confidence: 99%
“…5e ). Thioflavin T (ThT) is widely used to follow amyloid fibril formation via fluorescence measurements 45 and has shown potential to follow other types of protein fibrils 64 , 65 . Insulin, which is known to form amyloid fibrils upon shaking at 40 °C 79 , was used as a positive control.…”
Section: Resultsmentioning
confidence: 99%
“…Supramolecular assembling peptides have served as an inspiration for the design of new peptides with the desired functionality 37 42 . The study of anti-microbial polymers has mainly focused on their synthetic design to overcome challenges in immunogenicity, off-target effects and serum instability and ensure their controlled release 43 45 . The most prominent self-assembling AMPs are the MAX peptides, a group of designed peptides, that form an injectable hydrogel by undergoing a transition from an unstructured soluble form to a self-assembling β-hairpin 46 53 .…”
Section: Introductionmentioning
confidence: 99%
“…Molecular self-assembly of biomolecules renders a route to nanofabrication and is an excellent chemical methodology to design a new class of nanostructured materials. Proteins and peptides, as building blocks for supramolecular self-assemblies, are particularly important for the fabrication of different biomimetic functional materials. , Contrary to complex protein molecules, small peptides have more control over the different noncovalent interactions responsible for the formation of self-assembled supramolecular structures. , The ease of peptide synthesis and manipulation as well as control over peptide length enable fabrication of different nanostructured materials such as nanofibers, nanoribbons, nanotubes, nanorods, and vesicles having different sizes and properties. Such self-assemblies are commonly used to produce different soft biogenic materials with various tunable properties in nanotechnology and medicine. For example, the pendent groups on the surface of self-assembled peptide nanocarriers have been tuned for site-specific drug delivery. , It has also been demonstrated that the assembly inspired from Aβ 42 peptide can be used to provide a scaffold for stem cell differentiation . In addition, the nanoscale peptide assembly has been reported to exhibit significant pyroelectric activity along with other physical properties. , …”
Section: Introductionmentioning
confidence: 99%